A 20 Gbps PAM4 data transmitter ASIC for particle physics experiments. (1st March 2022) - Zhang, L.; Cruda, E.M.; Chao, C-P.; Chen, S-W.; Deng, B.; Francisco, R.; Gong, D.; Guo, D.; Hou, S.; Huang, G.; Huang, X.; Kulis, S.; et al.
Abstract: We present the design and test results of a novel data transmitter ASIC operating up to 20.48 Gbps with 4-level Pulse-Amplitude-Modulation (PAM4) for particle physics experiments. This ASIC, named GBS20, is fabricated in a 65 nm CMOS technology. Two serializers share a 5.12 GHz Phase Locked Loop (PLL) clock. The outputs from the serializers are combined into a PAM4 signal that directly drives a Vertical-Cavity-Surface-Emitting-Laser (VCSEL). The input data channels, each at 1.28 Gbps, are scrambled with an internal 2 7 -1 Pseudo-Random Binary Sequence (PRBS), which also serves as a frame aligner. GBS20 is tested to work at 10.24 and 20.48 Gbps with a VCSEL-based Transmitter-Optical-Subassembly (TOSA). The power consumption of GBS20 is below 238 mW and reduced to 164 mW in the low-power mode.